Analisis Ripple Voltage pada Rangkaian Half-Wave Rectifier dan Full-Wave Rectifier Menggunakan Kombinasi Filter Kapasitor dan Resistor - N., Andi Rosman (Universitas Negeri Makassar, 2023)
The aim of this research is to investigate and analyze the ripple voltage in half wave and full wave rectifier circuits with a focus on the use of a combination of capacitor and resistor filters. This research is experimental research using Circuit Wizard. The tools and materials used include CT transformers, diodes, resistors, capacitors, multimeters, alternating power sources, and oscilloscopes. The research process begins by designing and implementing a circuit in the Circuit Wizard simulator according to the concept of half wave and full wave rectification with capacitor and resistor filters. The research results show that to produce a small ripple voltage, use large capacitance and resistance values. The best ripple voltage value produced is 0.6 V when using a 150 mF capacitor or 1000 Ohm resistor.